The Impact of Increase in Value Added Tax and E-Commerce Transactions on Preference Expenditure Generation Z on the Shopee Platform - Pradhita Andira Dianastari; Aminah (International Journal of Economics, Business and Innovation Research, 2026)
This research aims For to determine the impact of the increase in Value Added Tax (VAT) and e-commerce transactions on preference expenditure Generation Z on the e-commerce platform Shopee. In today’s digital era, Generation Z demonstrates high dependence on online shopping platforms, even in the midst of policy fiscal such as the increase in VAT. This study uses a quantitative approach with a survey method. Against 100 respondents Generation Z who actively use Shopee. The data analysis technique used was multiple linear regression. Through help device SPSS software version 25. Research results shows that the increase in VAT has an impact positive and significant to preference expenditure, which indicates that the increase taxes do not hinder Generation Z in allocating funds for consumption. In addition, e-commerce transactions also have a positive and significant impact to preference expenditure. Simultaneously, both variables​ together influence preferences expenditure Generation Z. These findings indicate that comfort, need, and proximity Generation Z with technology become factor main factor that is more dominant than the other factors additional costs such as tax. This research contributes to​ perpetrator businesses and governments in designing targeted digital marketing and tax strategies.